Strategic Management Study: Analysis of the Impact of Digital Marketing on Increasing Sales Volume of K-pop Ticket Concierge Services - Irawanty, Wulan Sergi; Khoiriyah, Laila; Purnamasari, Pupung (Growth: Journal Management and Business, 2024)
This study aims to analyze the influence of digital marketing on the increase in the sales volume of K-pop ticketing services in Indonesia. With the growing K-pop trend and the high demand for concert tickets, ticket pick-up services are a solution for fans who find it difficult to get tickets in person. In this study, a quantitative approach was used to collect data from respondents involved in the ticketing service business on social media and e-commerce platforms. Data was collected through questionnaires which were then analyzed using linear regression analysis techniques. Engaging content, direct interaction with customers, and strategy adjustments based on data analytics also contribute to increased sales volume.Digital marketing elements, such as the use of social media, marketing content, paid advertising, and data analytics, have a significant influence on sales volume. The use of social media as the main marketing platform has a positive impact in reaching potential customers and building loyalty. However, challenges such as changes in social media algorithms and fierce competition need to be overcome by businesses with adaptive strategies.